LMN Facial Palsy in Pregnancy: An Opportunity to Predict Preeclampsia-Report and Review - Vani Aditya (Hindawi Limited, 2014)
Facial paralysis is the most frequent unilateral cranial nerve pathology affecting pregnant population 2 to 4 times more often than the nonpregnant population. There exists an association with preeclampsia but this has largely been overlooked. Clinicians often dismiss it for idiopathic palsy as seen in the present case. A 30-year-old woman, Gravida 4, Para 3, presented at 26 weeks pregnancy with complaints of facial weakness, blurring of vision, altered taste sensation, increased noise sensitivity for 1 month, headache since 18 days, and vomiting since 23 days. Her pulse was 90/min, BP was 170/120, and RR was 18/min. Uterus was 18 weeks size and proteinuria++ was present. Ultrasonography revealed a 26 weeks fetus, severe bradycardia, and absent liquor. HELLP syndrome was diagnosed after investigations. Six units of fresh frozen plasma were transfused. An informed decision for termination of pregnancy was made. She delivered a 450 gram stillborn. The third stage was complicated with postpartum hemorrhage but it was managed successfully. Women with Bell's palsy during pregnancy should be evaluated critically as in some it may precede preeclampsia which has serious maternal and fetal implications. Therefore, these women should be in regular followup of the obstetrician.